CONTINUOUS IMPROVEMENT STRATEGY - Mora, Jose Nicolas Cardona (European Scientific Journal, ESJ, 2014)
Nowadays the companies live in a constant changing world where customers demand better products, higher quality and shorter delivery times. To achieve these customers requirements companies rely on Continuous Improvement to reach their goals but without having a clear strategy for it. In this paper it is discussed in a literature review, the origin, definition and most used tools of CI. Then it is analyzed if the Learning School for strategy fits with CI to help in the creation of a strategy for CI.